Планування соціально-економічних заходів з розвитку компетенцій працівників підприємств в умовах міжнародної економічної діяльності - Лема, Г. В.; Олексів, І. Б.; Лісович, Т. Ю.; Lema, H.; Oleksiv, I.; Lisovych, T. (Видавництво Львівської політехніки, 2018)
Розглянуто ефективність оцінювання компетенцій працівників підприємств. На основі запропонованих заходів розвитку компетенцій працівників в умовах обмеженого ресурсного забезпечення побудовано економіко-математичну модель, яка передбачає вирішення різноманітних проблем з підвищення рівня розвитку компетенцій працівників, що, свою чергою, впливає на рівень ефективності інноваційної діяльності підприємств.

The article considered the effectiveness of evaluation employees competencies of enterprises. On the basis of the proposed measures for the development of employees competencies in the conditions of limited resources, an economic-mathematical model is proposed that involves solving various problems in improving the level of development of employees competences, which in turn affects on the level of the innovation activity efficiency of enterprises. The system of development the employees competence on enterprises, proposed in the article, is not only theoretical development of authors, but it can also be applied in practice to solve various problems. In particular, problems related to raising the level of development the employees competences, which in general affects on the level of innovation and international activities efficiency of enterprises. In addition, the proposed evaluation system will enable officials in the short term to get information of the level of competence of employees, and will allow the development and implementation of certain measures to improve them in terms of innovation development and international enterprise activity. It is worth noting that the untimely or biased process of evaluating the effectiveness of employees competencies may negatively affect the formation on the competitiveness of the enterprise, in particular in the context of international economic activity. Also, the article provides a comparative analysis of the basic methods used to collect and accumulate information. The integrity and adequacy of the information collected plays a decisive role in the formation of a strategic plan for the development of competences for enterprise employees.
Planning social-economic actions of the competences development of employees in conditions of international economic activity
Keywords: знання; уміння; навички; компетенції; працівники; заходи з підвищення компетенцій; knowledge; skills; competence; employees; measures to increase competencies; 658; 005.95